Effect of promoter in hierarchical hollow Pt/Beta catalysts on the hydrodeoxygenation of phenol. (1st June 2022) - Liu, Yuxiang; Yu, Hai; Fu, Yingying; Liu, Xinchun; Guo, Delin; Li, Shuo; Tao, Shuo; Lyu, Yuchao; Wang, Xiaosheng; Yu, Hailong; Yu, Shitao
Highlights: Hierarchical hollow Beta molecule sieves are prepared. A competitive adsorption of cyclohexene on catalysts affects the conversion of phenol. Acidity regulation is important for dehydration and inhibit coke deposition. Abstract: An efficient hydrodeoxygenation (HDO) catalyst (i.e., Pt/Beta) is designed to improve the quality of bio-oil by removing chemicals with oxygen-containing functional groups (e.g., phenol). Hierarchical hollow Beta molecular sieves are obtained via an alkaline treatment with surfactants (i.e., dodecyl trimethyl ammonium bromides (DTAB) and stearyl trimethyl ammoium bromide (STAB)). Surfactants adsorb on the surface of zeolitic surface to inhibit alkaline etching and finally to form a hollow morphology. A competitive adsorption of phenol on acid and metallic sites is observed on Pt/Beta catalysts. A large amount of Brønsted acids with a higher acidic strength have a stronger adsorption ability of phenol. Therefore, more metallic sites are required to provide adsorption and HDO sites for phenol molecules. As for cyclohexane, more acids with a higher acidic strength are desired. However, coke covers acid sites and inhibits the dehydration reaction. These results provide a hierarchical hollow molecular sieves preparation method and propose the importance of acid regulation in the design of HDO catalysts.